Znaczenie ładu liczbowego oraz muzyka jako dar Boży w świetle traktatów Andreasa Werckmeistra - Korpanty, Katarzyna (Muzyka, 2016)
The organist, composer and music theorist Andreas Werckmeister (1645–1706) is an important figure in the history of german music of the seventeenth and early eighteenth centuries. His name was well-known throughout Protestant Germany, even though he never travelled far and spent his entire life in the Harz region. Werckmeister was regarded as a great authority in the field of organ building. He wrote eleven treatises, one of which is lost. In his writings, Werckmeister discussed issues related to pipe organ manufacturing and musical temperament, the teaching of composition and basso continuo, and also musical-philosophical matters. His works were held in very high regard, including by the composer Dietrich Buxtehude and such theorists as W.C. Printz, J.G. Ahle, J.G. walther, J. Mattheson and J. Adlung. The views formulated by Werckmeister were characteristic of the German music theory of the seventeenth century. Two of his conclusions are very significant. First, music is a mathematical field of knowledge based on numerical proportions. Throughout the Baroque era, German thinkers perpetuated a worldview derived from Pythagoras and Plato, according to which all reality was governed by mathematical principles. Werckmeister placed particular emphasis on the importance of the harmony of numbers in the structure of the universe, including music. Within this context, he discussed the issues of musica mundana and musica humana, and set out rules for teaching composition. His other vital conclusion was that music was a gift of God that should be appreciated. Werckmeister was a pious Protestant, and it was Lutheranism that influenced him the most. Like Luther, he believed that music brings us closer to God. In his writings, he often expressed his regret that his contemporaries treated music with contempt and misused it. He wrote at length about the reasons for that state of affairs. Werckmeister emphasised that the only legitimate purpose of all music – sacred and secular, vocal and instrumental – was to glorify God. In his opinion, music that served any other purpose or lacked order was an act of gross abuse.